(untitled) (Zaporizhzhia Historical Review, 2021)
The article dwells upon the essence of social, political and economical changes taking place in Ukraine after proclaiming its independence in the August 1991. The author rejects the wide-spread conceptions of these changes as: 1) national-democratic revolution, or 2) international imperialistic “conspiracy”. The author supports the point of view of those specialists who considers the events connected with proclaiming Ukrainian independence as an “unfinished revolution”.